Implementation of the National Health Insurance Programme in Achieving Universal Health Coverage in Indonesia - Alkayyis, Muhammad Youri (BPJS Kesehatan, 2024)
Many countries have agreed to and enforced the implementation of Universal Health Coverage (UHC), yet achieving it is only occasionally seen in certain countries. The National Health Insurance (JKN) Programme is an Indonesian government initiative aimed at providing health protection to all residents of Indonesia through the JKN Programme. The oversight of the Programme and its pivotal role in Indonesia's pursuit of Universal Health Coverage (UHC) is managed by the Social Health Insurance Administration Body (BPJS Kesehatan). The objective of the JKN Programme is to furnish the populace with healthcare services and monetary safety. In Indonesia, the JKN Programme represents a concrete endeavour towards realising universal health coverage through the facilitation of health accessibility, financial safeguards, and the enhancement of healthcare service quality for all individuals. Based on this paper's foundation, this study aims to assess how the JKN Programme in Indonesia has been utilised to achieve UHC and identify the factors contributing to its success through a Systematic Literature Review (SLR). The methodology utilised in this research is the literature review approach. This investigation analysed research results linked to the subject matter being studied. Recent journals published between 2019 and 2023 were identified as the data sources for the literature review.